Effect of Interpersonal Injustice on Knowledge Hiding Behavior: Moderating Role of High-Performance Work Stress - Cao, Yi (Frontiers in Psychology, 2022)
The underlying aim of this study was to investigate the impact of interpersonal injustice on emotional exhaustion and the three main facets of knowledge hiding i.e., evasive knowledge hiding, playing dumb, and rationalized knowledge hiding. This study also undertook to observe the moderating role of high-performance work stress in the relationship between interpersonal injustice and emotional exhaustion. A questionnaire technique was adopted to obtain data from 539 employees working in the telecom sector of China. The Smart-PLS software was used to analyze the data through the aid of a structural equation modeling (SEM) technique. The results revealed that interpersonal injustice had a positive and significant relationship with evasive knowledge hiding, playing dumb, and rationalized knowledge hiding. Interpersonal injustice also had a positive relationship with emotional exhaustion and, it was found that emotional exhaustion was has a positive relationship with evasive knowledge hiding, playing dumb, and rationalized knowledge hiding. The results also revealed that emotional exhaustion mediated the relationship between interpersonal injustice and knowledge hiding (evasive hiding, playing dumb, and rationalized hiding). Moreover, it was also observed that high performance work-stress moderated the relationship between interpersonal injustice and emotional exhaustion. Theoretical, this paper made a valuable contribution by examining the impact of interpersonal injustice on knowledge hiding behavior. In terms of practical implications, this paper would certainly aid the organization to support a fair and just workplace culture that encourages knowledge sharing. Moreover, this paper would also aid in addressing problems associated with workplace stress and emotional wellbeing at the workplace.